Formulating business strategy for â€œallstar agencyâ€ in order to become a market leader - Gozali, Kenny; Toha, Mohamad (The Indonesian Journal of Business Administration, 2016)
Abstract.Â  Allstar coorperation is a company which operates as an insurance agency, agency Allstar is part of Prudential Life office sales force in Indonesia, based in Jakarta, so that the product sold by Allstar are Prudential life insurance. Allstar as a new agency stood at the date of January 9, 2015, by the three founder Oei Hong Tzan, Dendy Gunawan, David Gozali At the time of the end of 2015 Allstar agency made a breakthrough in Prudential Indonesia, having just stand can reach the 6th position in Indonesia beat agency that has a long standing and has been great from Allstar agency. Allstar agency after seeing a performance and a great result in the last year saw an opportunity and believe that can reach the position 1 in Indonesia and could be a market leader in Indonesia. To achieve these goals it is necessary to analyze the strategy right, and put on filling the questionnaire of customer Allstar own view peforma agent Allstar, and also filling the questionnaire agent Allstar to see a performance agency Allstar, because this is a service business importance level and performance level is associated, and if the result is nice to be sustainable and can even thrive, because mendaptkan references from satisfied customers. In this business the agent is very important, if the team owned small will greatly affect the turnover that get it for Allstar agency, because the annual turnover Allstar agency is a collection of the turnover that get it from the team Allstar, and revenue Allstar agency around 10% of annual turnover. Therefore, external and internal analysis is very influential. And the results of the analysis of external as well as internal and also the results of the questionnaire will be used in planning strategies for Allstar agency to deal with the live market from competitors and also make business canvas new one in order to increase the strength and also the opportunities that are useful in the formation and strategic planning Allstar fits within this agency.